PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN APOTEK CANGKIRAN - Lestari, Nadia Anggi; Erki Arfianto; Ningtyas, Ery Ardiyanti (Universitas Imelda Medan, 2024)
Health is an important factor in life because with health, everyone is able to carry out activities smoothly without any interference (Kuniano, 2015). To support this health, health facilities are needed, one of which is a pharmacy. A pharmacy is one of the pharmaceutical service facilities as a place of practice for pharmacists. Pharmacy practitioners must know how to make pharmaceutical activities provide satisfaction and benefits for patients or consumers by providing complete drug information, comfortable facilities, communicating in easy-to-understand language, being able to understand consumer needs, appearing polite and courteous, friendly in conveying information, and providing fast and precise service to patients or consumers. Customer perceptions of prices, for example expensive, cheap or appropriate, have a strong influence on purchasing interest and purchase satisfaction (Herlina & Tugiono, 2021). The aim of the research was to ascertain how customer satisfaction at Cangkiran Pharmacy is impacted by pricing and service quality. However, it should be based on an Islamic perspective for pharmaceutical service activities to run with blessings and goodness. This research uses a quantitative approach method, which is a process of seeking knowledge with data in the form of numbers as a tool in analyzing information related to something to be known. Data is collected through the use of written questions (questionnaires).